Geochemical characteristics and hydrocarbon generation potential of main source rocks in the Upper Triassic Xujiahe Formation, Sichuan Basin, China - Wang, Zhihong; Hao, Cuiguo; Jin, Hui; Cui, Junfeng; Wu, Xueqiong; Bo, Dongmei; Su, Yiqing (Frontiers in Earth Science, 2023)
In order to have a comprehensive understanding of the characterization and hydrocarbon generation potential of the source rock in the Upper Triassic Xujiahe Formation, Sichuan Basin, the geochemical data of more than 1,500 cuttings and 106 core samples were collected and analyzed. The T3x5 member of Xujiahe formation show the highest average TOC content (3.63%) followed by the T3x1+2 and T3x3 members. The TOC contents of different members show a general decreasing trend from the bottom to the top in Xujiahe formation. From the rock pyrolysis and kerogen δ13C values, the source rock trend to be kerogen type III with minor amounts of type Ⅱ2. According to the Ro values, the Xujiahe source rock shows high maturity in the northwest and low maturity in the southeast. Most of the source rock in T3x1+2 members are in high to overmature stage, while most of the source rock in the T3x3 and T3x5 member are in the mature to high mature stage. By comparing the burial history and hydrocarbon generation evolution history of source rocks in central and western Sichuan basin, it can be found that the sedimentation rate differences during the Cretaceous period is the main cause of the thermal evolution difference of the source rock. The gas generation intensity and quantity of different members are also compared. The T3x5 member show the highest gas generation potential followed by the T3x31 and the T3x1+2 members. In general, horizontally, the source rock of Xujiahe formation in Sichuan Basin is characterized by great thickness, high maturity, and high gas generation intensity in the northwest, which are gradually decrease to the southeast. Vertically, the T3x5 member show the highest gas generation content, which account for 39.6% of the total amount.